Herramientas digitales para la cultura organizacional de la empresa la ganga del cantón Quito, provincia de Pichincha. - Camacho Bonilla , Jenny Carolina (2023)
The objective of this research project was to identify the digital tools to strengthen the organizational culture of the employees of the company "La Ganga" in the city of Quito, Province of Pichincha; a quantitative approach and a non-experimental design were adopted to analyze how digital tools influence the organizational culture, considering that the latter is based on the company's philosophy. The methodology used is based on conducting surveys to the organization's collaborators, using a questionnaire designed specifically for this purpose. The questionnaire addresses two main variables: organizational culture and digital tools. In relation to organizational culture, it explores how the company's values, beliefs and norms influence employee interactions and behaviors. In addition, it explores how the philosophy of "La Ganga" is reflected in its internal culture. On the other hand, the use and perception of digital tools in the work environment is analyzed. It is investigated how the adoption of digital technologies impacts communication, collaboration and efficiency within the company. In addition, it is evaluated whether the integration of these tools is aligned with the values and principles of the organization. Through this quantitative approach, we seek to establish connections between the use of digital tools and key aspects of organizational culture. While no variables are manipulated in an experimental setting, valuable insights will be gained into how digital tools can strengthen or challenge the existing culture. The results can provide valuable guidance for decision making related to organizational culture management and the implementation of digital tools in the work environment.